APLIKASI EVALUASI PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF MENGGUNAKAN PHP DAN MYSQL - SU KAM TO (STKIP PGRI Tulungagung, 2017)
This research discusses the evaluation or online exam using the computer interactively. This system is not using paper or print media, but only uses a set of computer and connected to the network, Â so the students can carry out the exam anytime and anywhere. The lecturers or admins do not need paper and correct test results for Quiz, Midterm Exam, and Final Exam. The Quiz, Midterm Exam and Final Exam are automatically corrected by the system, and then making it easier for lecturers to process values. This application was created using FLASH, PHP and MySQL as the database. This application was designed using Unified Modeling Language (UML), that are Use Case, Class, Activity, and Sequence DiagramsÂ Keywords: Evaluation, Flash, MySQL, PHP, and System